Pengembalian Barang Hutangan dengan Format Gotong Royong dalam Pembangunan Rumah - Ach. Fadlail; Nur Hasana (Program Pascasarjana Universitas Ibrahimy, 2019)
Islam has taught all aspects of life, both of ritual worship and muamalah, worship which is needed to maintain the strength and harmony of human relations as servants with to Allah, while muamalah is said to be rulers of the game. It is one of the noble cultures of the Indonesian people which is always inherited and continues to be preserved from generation to generation until now, from this togetherness a tradition emerges in some societies known as